Stature and body weight estimations from footprint dimensions among asante and fante females in Ghana - Samuel Kwaku Dwomoh; Atta Kusi Appiah; Nancy Darkoa Kusi Appiah; Chrissie Stansie Abaidoo (Wolters Kluwer Medknow Publications, 2023)
Background: Footprints recovered from crime scenes can assist in establishing the identity (stature, body weight, and sex) of a person. Due to variations (genetic and environmental factors) in the morphology of the foot, several authors have derived populationspecific regression equations for stature and weight estimations. Aims and Objectives: Tribal differences in the footprint dimensions of Ghanaians have not been established. Hence, this study was done to determine if they were tribal differences in footprint dimensions. Materials and Methods: The footprints of Ghanaian females, aged 19-35 years, and belonging to two tribal groups (72 Asante and 73 Fante) were recovered using an ink pad method. Height, body weight, and footprint measurements were obtained following standard procedures. Results: Although Fante females had longer foot lengths and shorter foot breadths than Asante females, the difference was significant (P < 0.001) only in the left big toe-pad length (eta squared = 0.496). Height correlated better with footprint dimensions of Fante (r = 0.246 - 0.809) than Asante (r = 0.214 - 0.660) females. Body weight correlated weakly with footprint dimensions. Unlike in Asante females, foot length measurements did not correlate significantly with body weight among Fante females. Conclusion: The use of mixed population in deriving stature, weight and sex equations is cautioned especially when there is increased genetic diversity. The findings of this study have important applications in forensic anthropometric investigations.